2015
DOI: 10.5539/enrr.v6n1p35
|View full text |Cite
|
Sign up to set email alerts
|

Oil-Water Adsorptive Properties of Chemically Treated Sugarcane Bagasse

Abstract: Among the contaminants plaguing our waters today, oil remains one of the most pervasive and challenging contaminant to remove. Oil pollution occurs not only through factory discharge, but also by accident spills from the fuel of the vehicle or the transportation of oil. Sugarcane bagasse (SB) is an abundant agricultural by-product containing almost half of cellulose and one quarter of lignin. After chemical treatments SB can be modified their hydrophobicity leading to improve its oil adsorptive properties. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Such affinity is common for natural fibers, which tend to absorb water and get swollen [31]. Djati Utomo et al [32] reported a similar water sorption of about 15 g/g for sugarcane bagasse. Even though a similar trend has been detected for milled fibers, the increase of specific surface has drastically enhanced the oil sorption capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Such affinity is common for natural fibers, which tend to absorb water and get swollen [31]. Djati Utomo et al [32] reported a similar water sorption of about 15 g/g for sugarcane bagasse. Even though a similar trend has been detected for milled fibers, the increase of specific surface has drastically enhanced the oil sorption capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Sugar cane composed of 48% cellulose, 28% hemicellulose, 21% lignin, 6% extractive and 3% ash [11]. It includes some functional groups that can be improved the oil adsorption [12].…”
Section: Introductionmentioning
confidence: 99%